2001
DOI: 10.1002/jpp.387
|View full text |Cite
|
Sign up to set email alerts
|

A survey of acid catalysts in dipyrromethanecarbinol condensations leading to meso-substituted porphyrins

Abstract: ABSTRACT:The successful use of dipyrromethanecarbinols in rational routes to porphyrinic macrocycles requires catalysis conditions that enable irreversible condensation, thereby avoiding substituent scrambling and formation of undesired porphyrin products. Previously, successful conditions of trifluoroacetic acid (TFA) (30 mM) in acetonitrile were identified following a lengthy survey of TFA and BF 3 -etherate catalysis in diverse solvents. In this study, focus was placed on the acid catalyst by examining 17 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(126 citation statements)
references
References 12 publications
2
123
0
1
Order By: Relevance
“…The synthesis of A 3 B-porphyrin 3 [15] and trans-A 2 BC-porphyrin 6 [27] has been described previously, where the critical dipyrromethane + dipyrromethane-dicarbinol condensation was performed using TFA in acetonitrile. Herein, we performed the condensation under new acidic conditions (InCl 3 or Yb(OTf) 3 in CH 2 Cl 2 ) [30]. The requisite dipyrromethanes (2, 5) [31] and diacyldipyrromethanes (1, 4) [32] were readily available.…”
Section: Synthesismentioning
confidence: 99%
“…The synthesis of A 3 B-porphyrin 3 [15] and trans-A 2 BC-porphyrin 6 [27] has been described previously, where the critical dipyrromethane + dipyrromethane-dicarbinol condensation was performed using TFA in acetonitrile. Herein, we performed the condensation under new acidic conditions (InCl 3 or Yb(OTf) 3 in CH 2 Cl 2 ) [30]. The requisite dipyrromethanes (2, 5) [31] and diacyldipyrromethanes (1, 4) [32] were readily available.…”
Section: Synthesismentioning
confidence: 99%
“…Preliminary accounts of this study have reported the optimal yields of TPP and NC-TPP for each acid [38], and the discovery of reaction conditions for the synthesis of NC-TPP in yields of ~40% [39]. In addition, we have recently found that a subset of the acids examined in this study is applicable to condensations with dipyrromethanecarbinol species [40]. This broad examination of acid catalysis provides a greater understanding of porphyrin-forming reactions and opens a wider set of options for addressing synthetic challenges.…”
Section: Introductionmentioning
confidence: 78%
“…One such example is the efficient synthesis of NC-TPP using methanesulfonic acid [39], a feat not possible with TFA or BF 3 -etherate catalysis [7]. Another example is our recent application of acids [Yb(OTf) 3 , Dy(OTf) 3 , Sc(OTf) 3 , and InCl 3 ] in condensations involving dipyrromethane-carbinols; these acids are poorly suited for the preparation of porphyrins by pyrrole-aldehyde condensations but are very effective with the more reactive dipyrromethane-carbinols, affording porphyrins bearing specific patterns of meso-substituents with minimal or no detectable scrambled products [40].…”
Section: Discussionmentioning
confidence: 99%
“…IR spectra were recorded on a Perkin-Elmer Spectrum 100 FT-IR spectrometer. Starting Materials: Formylporphyrins 1a, [29] 1b; [30] bromoporphyrins 4a, [31] 4j, [32] 4l; [31] dipyrromethane [15] , 5,15-disubstituted porphyrins: 8a, [33] 8b, [14b] 8c, [34] 8d, [14b] 8e, [35] 8f, [36] 10a, [37] 5,10,15-triphenylporphyrin 9a and the nickel(II) complex 11a, [39] and 5,15-bis(4-methylphenyl)-10-phenylporphyrin (9b) [40] were prepared using standard methodologies and had analytical data consistent with that in the literature. General Procedure A.…”
Section: Methodsmentioning
confidence: 99%